MENGUKUR TINGKAT PARTISIPASI MASYARAKAT KOTA GUNUNGSITOLI TERHADAP PROGRAM PENGELOLAAN SAMPAH REDUCE, REUSE, RECYCLE (3R) - SUARTRI WELI KRISMEINAR HAREFA (Departemen Sosiologi Universitas Sumatera Utara, 2012)
Abstract A Trash problem is a problem that will continue to evolve and the proceeds, more and more human activity will affect the amount of generated trash production. Society as trash producers have a role in keeping the environment clean. The purpose of this study was to measure the level of community participation in the trash management programs reduce, reuse, recycle (3R). The level of community participation seen from the level of knowledge and community action Gunungsitoli the 3R. In this study, will be seen the relationship between participation, knowledge and action. This study uses the theory of BF Skinner's about behavioral and social action theory Max Weber. The research method is a method of quantitative survey and describe the level of participation. The results showed that people Gunungsitoli have a good level of participation, but participation was not supported by a good management of trash system or reinforcement participation. Keywords: Participation, Community, Management, Trash, 3R Program